USING A LABORATORY-BASED CUMULATIVE DEFICITS INDEX TO EXAMINE THE IMPACT OF TOTAL PATHOGEN BURDEN - Noppert, G (Innov Aging, 2018)
Background: Detecting underlying biological wear and tear prior to diagnosed clinical dysfunction is increasingly providing clues to the aging process. Few studies have examined pathogen burden, a measure of the cumulative effects of multiple persistent pathogens, as potentially accelerating the pace of age-related biological decline by midlife. Methods: Using data from two waves of the National Health and Nutrition Examination Survey, we compared three alternative methods for measuring pathogen burden, composed of mainly persistent viral infections, using a cumulative deficits index (CDI) as an outcome: single pathogen associations, a pathogen burden summary score, and latent class analyses. The CDI was constructed by summing the number of 28 biomarkers (i.e. white blood cell count, calcium, etc.) for which an individual was in the dysfunctional range. The study sample was aged 20–49 years old. Seven pathogens were assessed in wave 1; five in wave 2. Results: We found significant heterogeneity in the distribution of the CDI by age, sex, race/ethnicity, and education. There was an association between pathogen burden and the CDI by all three metrics. The latent class classification of pathogen burden showed particularly strong associations with the CDI. Conclusions: Our results suggest that pathogen burden may influence early clinical indicators of poor health as measured by the CDI, even in a relatively young population. These findings suggest that reducing pathogen burden and the specific pathogens that drive the CDI may provide a target for preventing the early development of age-related physiological changes.